Tailoring the mechanical and biodegradable properties of binary blends of biomedical thermoplastic elastomer. (March 2018) - Ang, Hui Ying; Chan, Jingni; Toong, Daniel; Venkatraman, Subbu S.; Chia, Sing Joo; Huang, Ying Ying
Abstract: Blending polymers with complementary properties capitalizes on the inherent advantages of both components, making it possible to tailor the behaviour of the resultant material. A polymer blend consisting of an elastomer and thermoplastic can help to improve the mechanical integrity of the system without compromising on its processibility. A series of blends of biodegradable Poly(L-lactide-co-ɛ-caprolactone) (PLC) and Poly-(l, l-lactide-co-glycolic acid) (PLLGA), and PLC with Poly-(d, l-lactide- co -glycolic acid) (PDLLGA) were evaluated as a potential material for a biodegradable vesicourethral connector device. Based on the Tg of the blends, PLC/PLLGA formed an immiscible mixture while PLC/PDLLGA resulted in a compatible blend. The results showed that with the blending of PLC, the failure mode of PLLGA and PDLLGA changed from brittle to ductile fracture, with an significant decreas in tensile modulus and strength. SEM images demonstrated the different blend morphologies of different compositions during degradation. Gel Permeation Chromatography (GPC) and mechanical characterization revealed the degradation behaviour of the blends in this order (fastest to slowest): PDLLGA and PLC/PDLLGA blends > PLLGA and PLC/PLLGA blends > PLC. The PLC/PLLGA (70:30) blend was recommended as a suitable for the vesicourethral connector device application, highlighting the tailoring of blends to achieve a desired mechanical performance. Graphical abstract: Schematics of proposed morphologies in the elastomer thermoplastic binary blends.fx1 Highlights: Blending an elastomer with thermoplastic polymers changes the mechanical behaviour. Poly(L-lactide-co-ɛ-caprolactone) (PLC) influences the ductility and strength of blends. Polymer morphology of the blends affects their mechanical behaviour during degradation.